2009
DOI: 10.1088/0268-1242/24/9/092001
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-level fabrication of GaN-based vertical light-emitting diodes using a multi-functional bonding material system

Abstract: We first report on the fabrication of 2 inch wafer-level GaN-based vertical light-emitting diodes (LEDs) by using a multi-functional bonding material system, which is composed of a thick Cu diffusion barrier and a bonding layer. The bonding material system superbly absorbs laser-induced stress and also effectively serves as a barrier to the indiffusion of Sn to the active region. Fully packaged vertical LEDs fabricated with indium tin oxide (ITO)/AgCu contact and the bonding material system give an operating v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…VLEDs have significant advantages over conventional lateral-type LEDs such as better current injection, excellent heat http://dx.doi.org/10.1016/j.spmi.2014.06.007 0749-6036/Ó 2014 Elsevier Ltd. All rights reserved. dissipation, and better reliability related to electrostatic discharge [1][2][3][4]. For the fabrication of GaNbased VLEDs, a variety of methods have been used, including laser lift-off [5]; chemical lift-off [6]; and growth on SiC [7] and Si substrates [8], after which the substrates are removed.…”
Section: Introductionmentioning
confidence: 99%
“…VLEDs have significant advantages over conventional lateral-type LEDs such as better current injection, excellent heat http://dx.doi.org/10.1016/j.spmi.2014.06.007 0749-6036/Ó 2014 Elsevier Ltd. All rights reserved. dissipation, and better reliability related to electrostatic discharge [1][2][3][4]. For the fabrication of GaNbased VLEDs, a variety of methods have been used, including laser lift-off [5]; chemical lift-off [6]; and growth on SiC [7] and Si substrates [8], after which the substrates are removed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a vertical GaN-based LEDs structure, which is fabricated with a combination of laser lift-off (LLO) and wafer bonding process, has been considered for high power lighting due to its advantages like uniform current spreading and excellent heat dissipation properties. [7][8][9][10] Conventional vertical LEDs require n-type Ohmic contacts to N-polarity n-GaN, but the structure is not desirable for high power applications due to poor Ohmic properties, thermal degradation, and decrease of effective surface area for light emission. Kim et al 11 suggested that Ti/Al Ohmic contacts to N-face GaN prepared by LLO process can cause severe degradation of contact resistance even at 400 C. By sharp contrast, vertical LEDs with Ohmic contact formation on Ga-polarity n-GaN before LLO process showed thermally stable contacts and increased the surface area relative to N-face GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] For VLEDs, the formation of reliable ohmic contacts on N-face n-GaN is very important since VLEDs contain a relatively small areal portion of n-electrodes (less than $10% of device area) 3 in addition to good p-type reflectors. 5,6 This implies that overall serial resistance is significantly affected by an increase in the n-contact resistance.…”
Section: Introductionmentioning
confidence: 99%